Hyper Democracy, Discombobulation: The United Kingdom Brexit: Itas Implication for Capitalism (Global Journal of Human-Social Science, 2016)
The paper is devoted to detail an analysis united kingdom s pull out of European Union economy called Brexit the aim is to look at the implication with an objective of preventing such political earthquake in further By way of qualitative analysis of relevant secondary source predicated on the Marxian assumption of the political economy the paper posits the dynamic of the politics of international economic relation as it is manifest between European Union EU and United Kingdom UK The paper argues that economic and political destiny of people should not be determined in such formulaic manner However political leaders who don t want sad outcomes only have to provide good leadership and meet the people s expectation before referendumism take place The paper recommend that British in the final analysis is yet to come to terms with certain of modern realities Nigeria can also be caught between nostalgia and their future Referendum should be a great lesson for Nigeria but it is highly recommended